F Formulasi dan Uji Stabilitas Sediaan Krim Ekstrak Bunga Melati Putih (Jasminum Sambac L.) Sebagai Anti Jerawat - Budianor Budianor; Siti Malahayati; Rina Saputri (LPPM Universitas Sari Mulia, 2022)
Background: White jasmine flower extract has antimicrobial activity against the growth of acne bacteria. To make it easier to use it is necessary to make pharmaceutical preparations, one of which is cream. The cream has the advantage that it is easy to apply to the skin, is not sticky and is easily washed off with water. Cream preparations were made with variations of adeps lanae base to obtain an optimal and stable formulation. The stability of the cream will be damaged if the mixture system is disturbed by changes in temperature, composition or the addition of one of the phases in excess. Objectives: To determine the optimal formulation and to analyze the physical and chemical stability of cream formulations with varying concentrations of adeps lanae base. Methods: This study used a true experimental design with a completely randomized design. The cream is formulated with various concentrations of adeps lanae, namely 3%, 5%, 8%. The stability test using the cycling test method included organoleptic tests, homogeneity, pH, adhesion, dispersibility, viscosity and emulsion type before and after. Results: The results showed that the variation in the concentration of adeps lanae did not show any difference in organoleptic, homogeneity, spreadability and emulsion type, but there were differences in pH, viscosity, and adhesion. The results of statistical tests showed a value of > 0.05 which indicated that there was no significant difference in the dispersion power and there was a significant difference in the value of <0.05 in pH, viscosity and adhesion to variations in the concentration of adeps lanae. Conclusion: The optimal formulation before the cycling test was formulation II and III with 5% and 8% base concentrations of adeps lanae. After the cycling test, the characteristic results showed that it was unstable. Variations in the concentration of adeps lanae on the cream base indicate that there are differences in physical and chemical stability.